The Effect of Utilizing Natural Environmental Resources on The Creativity and Fine Motor Skills of Children Aged 4–5 Years - Yunita, Lisa; Mayar, Farida; Suryana, Dadan; Mahyuddin, Nenny (Universitas Ahmad Dahlan, 2025)
This study aimed to examine the effects of utilizing natural environmental resources on the development of creativity and fine motor skills in children aged 4–5 years. A quantitative approach was employed using an experimental method with a 2×2 factorial design. The sample consisted of 20 children, who were divided into experimental and control groups. The experimental group participated in learning activities involving natural materials—such as painting, pasting, beading, and collage—using beach items like shells, stones, and sand. In contrast, the control group engaged in free drawing activities. Data were collected using observation sheets to assess children's creativity and fine motor development. Hypothesis testing revealed that the use of natural environmental resources had a significant effect on creativity (p = 0.008) and fine motor development (p = 0.003). Moreover, a significant combined effect on both developmental aspects was observed (p = 0.000), along with a positive interaction between the two. These findings suggest that natural environmental materials serve as effective educational tools for enhancing creativity and fine motor skills in early childhood learning settings.